Physical properties of diamond and sapphire - Aggarwal, R. L. (Roshan Lal), 1937-; Ramdas, Anant K. (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2019)
Focusing on the physical properties of diamond and sapphire, this monograph provides readers with essential details on crystal structure and growth, mechanical properties, thermal properties, optical properties, light scattering of diamond and sapphire crystals, and sapphire lasers. Various physical properties are comprehensively discussed: Mechanical properties include hardness, tensile strength, compressive strength, and Young's modulus. Thermal properties include thermal expansion, specific heat, and thermal conductivity. Optical properties of diamond and sapphire include transmission, refractive index, and absorption. Light scattering includes Raman scattering and Brillouin scattering. Sapphire lasers include chromium-doped and titanium-doped lasers. Aimed at researchers and industry professionals working in materials science, physics, electrical engineering, and related fields, this monograph is the first to concentrate solely on physical properties of these increasingly important materials.
OCLC-licensed vendor bibliographic record.
Keywords: Diamonds; Sapphires; NATURE / Rocks & Minerals; SCIENCE / Earth Sciences / Mineralogy; TECHNOLOGY / Material Science; SCIENCE / Physics; TECHNOLOGY / Electricity